Face/Off: The Interchangeable Side of Candida Albicans - Cottier, Fabien; Hall, Rebecca A. (Frontiers in Cellular and Infection Microbiology, 2020)
Due to limited mobility, fungi, like most unicellular organisms, have evolved mechanisms to adapt to sudden chemical and/or physical variation in their environment. Candida albicans is recognized as a model organism to study eukaryotic responses to environmental changes, as this human commensal yeast but also opportunistic pathogen responds to numerous environmental cues through switching morphologies from yeast to hyphae growth. This mechanism is largely controlled by two major pathways: cAMP-PKA and MAPK, but each environmental signal is sensed by specific sensors. However, morphological switching is not the only response C. albicans exerts in response to environmental cues. Recently, fungal cell wall remodeling in response to host-derived environmental cues has been identified as a way for C. albicans to manipulate the innate immune system. The fungal cell wall is composed of a chitin skeleton linked to a network of β-glucan, which anchors proteins and mannans to the fungal cell surface. As localized on the cell surface, these molecules drive interactions with the environment and other cells, particularly with host immune cells. C. albicans is recognized by immune cells such as neutrophils and macrophages via pathogen recognition receptors (PRRs) that bind different components of the cell wall. While β-glucan and mannan are proinflammatory molecules, chitin can induce anti-inflammatory responses. Interestingly, C. albicans is able to regulate the exposure of these pathogen-associated molecular patterns (PAMPs) according to environmental cues resulting in a modulation of the host immune response. This review describes the mechanisms involved in C. albicans response to environmental changes and their effect on immune recognition.